Imagining Twitter as an Imagined Community - Gruzd, Anatoliy; Wellman, Barry; Takhteyev, Yuri (The American behavioral scientist (Beverly Hills), 2011)
The notion of “community” has often been caught between concrete social relationships and imagined sets of people perceived to be similar. The rise of the Internet has refocused our attention on this ongoing tension. The Internet has enabled people who know each other to use social media, from e-mail to Facebook, to interact without meeting physically. Into this mix came Twitter, an asymmetric microblogging service: If you follow me, I do not have to follow you. This means that connections on Twitter depend less on in-person contact, as many users have more followers than they know. Yet there is a possibility that Twitter can form the basis of interlinked personal communities—and even of a sense of community. This analysis of one person’s Twitter network shows that it is the basis for a real community, even though Twitter was not designed to support the development of online communities. Studying Twitter is useful for understanding how people use new communication technologies to form new social connections and maintain existing ones.